Incidence of nonsyndromic congenital heart defects in the Republic of Srpska in the period 2015–2016 - Marić, Nina; Predojević Samardžić, Jelica; Djukic, Dario (Vojnosanitetski pregled, 2023)
Background/Aim. Congenital heart defect (CHD) is the most common type of birth defect and one of the leading causes of infant mortality. It can be isolated or occur as a part of multiple different syndromes. The reported worldwide incidence of isolated CHD is between 70 and 120 per 10,000 live births. The aim of the study was to estimate the incidence of nonsyndromic CHD in the Republic of Srpska (RS), Bosnia and Herzegovina and compare it with other countries. Methods. The fetuses, live-born and stillborn infants with CHD during 2015 and 2016 in the RS, were analyzed using data from a cross-sectional study. Results. The total incidence of CHD was 163.95 per 10,000 total births, and the incidence of live-born with CHD was 136.64 per 10,000. The diagnosis was established prenatally in 8.09% of cases. The most common type of anomaly was ventricular septal defect (45.63%), followed by an atrial septal defect (31.40%), patent ductus arteriosus (7.44%), and pulmonary valve stenosis (5.18%). A significant difference in the incidence of CHD between regions and different maternal age groups was found. Conclusion. The incidence of CHD in the RS found in this study is higher than in other studies, with marked heterogeneity between different regions. This study provides baseline data for future monitoring of the risk factor changes and the implementation of primary preventive measures.